Comparison of hypersensitivity reactions to carboplatin retreatment in gynecologic cancer patients between one and two hour infusions: A randomized trial study - Pornwattanakrilert W. (2017)
Objective: To compare the incidence rate of carboplatin hypersensitivity reactions (HSRs) in gynecologic cancer patients receiving one-hour or two-hour carboplatin retreatment infusions. Setting: A Prospective Randomized Controlled Trial. Methods: Recurrent gynecologic cancer patients 25 to 80-years of age who were scheduled to receive carboplatin retreatment after previously receiving at least six cycles of carboplatin without a history of platinum allergy were invited to enroll. They were randomized to receive either a one-hour or two-hour carboplatin infusion in each cycle. The nurses recorded any occurrence of HSR. Patients who developed carboplatin HSR were discontinued from the study. Results: Forty-five patients were enrolled and randomized to receive either a one-hour carboplatin infusion arm in 69 cycles or a two-hour infusion arm in 67 cycles. Both groups were well balanced regarding median age, body mass index, type of cancer, history of drug allergy, median platinum free interval time, median total number of previous carboplatin cycles, premedication type, regimen and median total dose of carboplatin. Five (3.67%) of the 136 cycles resulted in carboplatin HSR, all of which were Grade 1. Of these, four cycles developed HSR during the one-hour infusion and only one cycle with a two-hour infusion (P = 0.37). The onset of carboplatin HSR occurred within 30-105 minutes after infusion start. Conclusion: Extending the carboplatin infusion time to two hours from one hour did not significantly decrease carboplatin HSR.